CACHE Challenge #3: Targeting the Nsp3 Macrodomain of SARS-CoV-2 - Herasymenko, Oleksandra; Silva, Madhushika; Correy, Galen J.; Abu-Saleh, Abd Al-Aziz A.; Ackloo, Suzanne; Arrowsmith, Cheryl; Ashworth, Alan; Ban, Fuqiang; Beck, Hartmut; Bishop, Kevin P.; Bohorquez, Hugo J.; Bolotokova, Albina; et al. (American Chemical Society, 2026)
The third Critical Assessment of Computational Hit-finding Experiments (CACHE) challenged computational teams to identify chemically novel ligands targeting the macrodomain 1 of SARS-CoV-2 Nsp3, a promising coronavirus drug target. Twenty-three groups deployed diverse design strategies to collectively select 1739 ligand candidates. While over 85% of the designed molecules were chemically novel, the best experimentally confirmed hits were structurally similar to previously published compounds. Confirming a trend observed in CACHE #1 and #2, two of the best-performing workflows used compounds selected by physics-based computational screening methods to train machine learning models able to rapidly screen large chemical libraries, while four others used exclusively physics-based approaches. Three pharmacophore searches and one fragment growing strategy were also part of the seven winning workflows. While active molecules discovered by CACHE #3 participants largely mimicked the adenine ring of the endogenous substrate, ADP-ribose, preserving the canonical chemotype commonly observed in previously reported Nsp3-Mac1 ligands, they still provide novel structure-activity relationship insights that may inform the development of future antivirals. Collectively, these results show that multiple molecular design strategies can efficiently converge on similar potent molecules.